2001
DOI: 10.1034/j.1399-3011.2001.10975.x
|View full text |Cite
|
Sign up to set email alerts
|

Clavaspirin, an antibacterial and haemolytic peptide from Styela clava

Abstract: We cloned the precursor of a novel peptide from a cDNA library prepared from pharyngeal tissues of the tunicate, Styela clava. Its sequence predicted a histidine‐rich, amidated 23‐residue peptide (FLRFigSVIHGIGHLVHHIGVAL‐NH2) that we named clavaspirin. A synthetic clavaspirin was prepared and it was found that it killed Gram‐positive and Gram‐negative bacteria, permeabilized the outer and inner membranes of Escherichia coli, lysed phosphatidylglycerol (POPG) liposomes, and was potently haemolytic towards human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 31 publications
(49 reference statements)
2
4
0
Order By: Relevance
“…For example, in a study by Rathinakumar et al 31 , sheep and human erythrocytes show different haemolysis levels when exposed to AMPs (0.5, 5 and 15 µM), where sheep erythrocytes prove to be more resistant than human red blood cells 31 . Similar differences in haemolysis between bovine and human blood were reported by Lee et al 32 and Belokoneva and co-workers 30 . These preliminary studies indicate that the differences between mammalian erythrocyte sensitivity towards AMPs can be substantial and that the choice of potentially misleading toxicity controls can easily adversely affect the outcome or conclusions of a study 33 .…”
supporting
confidence: 86%
“…For example, in a study by Rathinakumar et al 31 , sheep and human erythrocytes show different haemolysis levels when exposed to AMPs (0.5, 5 and 15 µM), where sheep erythrocytes prove to be more resistant than human red blood cells 31 . Similar differences in haemolysis between bovine and human blood were reported by Lee et al 32 and Belokoneva and co-workers 30 . These preliminary studies indicate that the differences between mammalian erythrocyte sensitivity towards AMPs can be substantial and that the choice of potentially misleading toxicity controls can easily adversely affect the outcome or conclusions of a study 33 .…”
supporting
confidence: 86%
“…In H. roretzi , halocyamines A and B are synthesized by MCs (127), and their cytotoxic activity is likely related to the presence of diphenol rings that render them substrates for PO. S. clava MCs produce clavanins A–D, histidine-rich, α-helix peptides, and clavaspirin (128, 129). In the same species, five styelins, cationic antimicrobial peptides, were identified and isolated from hemocyte lysates (130, 131).…”
Section: Humoral Defensive Repertoirementioning
confidence: 99%
“…Clavaspirin, clavanins and styelins were isolated from another solitary tunicate, Styela clava and these pH dependent AMPs were found to be rich in both histidine and phenylalanine residues [68,69]. In general, it was found that clavaspirin and clavanins possessed pH dependent antibacterial and antifungal activity [65,66,67,76] with low pH, enhancing the ability of these AMPs to adopt α-helical structure and permeabilize the membranes of these organisms [68,69]. It appeared that the protonation of histidine residues under low pH conditions promoted the ability of these AMPs to target microbial membranes whilst the presence of their glycine and phenylalanine residues provided them with the conformational flexibility and structural hydrophobicity to facilitate bilayer partitioning [70,71,72,73,74,75].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%